Secularization, secularism and laicidade in Brazil: Rethinking global theoretical assumptions - Dullo, Eduardo (Religion compass, 2024)
Current studies on religion in Brazil are marked by the dispute over secularism and the boundaries between the religious and the political. This paper shows how the literature on secularization and laicidade followed the social relevance of religions to adjust the focus on the subjects under research to the point that throughout the 20th century, studies were mainly dedicated to analyzing the position of the Catholic Church vis-à-vis the national secular state; the growth of the Pentecostals since the mid-1990s, led to a shift in the literature dedicated to their new relevance in public life and their dispute over laicidade. I argue that this social transformation broadened the scope of the investigation to the particularities of their presence in the public sphere and the production of Pentecostal political-esthetic sensibilities, in contrast to the previous Catholic secularity pattern. This scenario of transformation with increased religious pluralism and conflict of public religions has enabled an understanding of the particularity of the experience of secularity in Brazil and allows us to rethink some of the previous global theoretical assumptions about secularization.